Germination niche breadth varies inconsistently among three Asclepias congeners along a latitudinal gradient. (10th June 2018) - Finch, J.; Walck, J. L.; Hidayati, S. N.; Kramer, A. T.; Lason, V.; Havens, K.
Abstract: Species responses to climate change will be primarily driven by their environmental tolerance range, or niche breadth, with the expectation that broad niches will increase resilience. Niche breadth is expected to be larger in more heterogeneous environments and moderated by life history. Niche breadth also varies across life stages. Therefore, the life stage with the narrowest niche may serve as the best predictor of climatic vulnerability. To investigate the relationship between niche breadth, climate and life stage we identify germination niche breadth for dormant and non‐dormant seeds in multiple populations of three milkweed ( Asclepias ) species. Complementary trials evaluated germination under conditions simulating historic and predicted future climate by varying cold–moist stratification temperature, length and incubation temperature. Germination niche breadth was derived from germination evenness across treatments (Levins Bn ), with stratified seeds considered less dormant than non‐stratified seeds. Germination response varies significantly among species, populations and treatments. Cold–moist stratification ≥4 weeks (1–3 °C) followed by incubation at 25/15 °C+ achieves peak germination for most populations. Germination niche breadth significantly expands following stratification and interacts significantly with latitude of origin. Interestingly, two species display a positive relationship between niche breadth and latitude, while the third presents a concave quadratic relationship. Germination niche breadth significantly varies by species, latitude and population, suggesting an interaction between source climate, life history and site‐specific factors. Results contribute to our understanding of inter‐ and intraspecific variation in germination, underscore the role of dormancy in germination niche breadth, and have implications for prioritising and conserving species under climate change.